Village Fund Accountability in Bogor Regency - Hermeilitha, Sofiana; Silitonga, Mala Sondang (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the accountability of village fund management in regional development in Bogor Regency, focusing on the five dimensions of accountability as proposed by Koppell’s theory: transparency, liability, responsibility, controllability, and responsiveness. The research employs a qualitative approach, using data collection techniques such as in-depth interviews, document analysis, and field observations involving key actors including the Village Community Empowerment Agency (DPMD), the Inspectorate, village heads, and local communities. The findings reveal that the principle of transparency has been implemented through the use of information media and digital systems such as SIPANDA and SITANTI. Both internal and external supervision mechanisms are actively in place, although not yet uniformly practiced across all villages. The study identifies key challenges in ensuring accountability, including the limited capacity of village officials, the weak role of the Village Consultative Body (BPD), and the insufficient level of community participation in planning and monitoring processes. The proposed strategies to enhance accountability include strengthening the capacity of human resources at the village level, optimizing the use of information technology, and providing incentives for villages that demonstrate accountable governance practices. The implications of this study emphasize that accountability is not merely about administrative reporting, but also reflects social responsibility and the sustainability of development efforts. These findings contribute to the formulation of village fund management policies that are more transparent, participatory, and results-oriented at the local level.